The Effectiveness Of Annotations In Computer Assisted Instructions (Cai) In Enhancing Science-Based Text Comprehension - Haliza Harun; Waidah Ismail; Siti Salhah Othman; Karmila Hanim Kamil (Universiti Sains Islam Malaysia, 2024)
The aim of this study is to investigate the effectiveness of annotations in nlultimedia on-screen texts using two presentational modes in enhancing learners comprehension level as well as vocabulary level. The subjects involved are 44 first year Biotechnology students of USIM. The methodology employed is experimental comparison of the performance of two groups of subjects under two different conditions: one using multimedia on-screen text with the annotations of 'text+animation' and the other using multimedia onscreen text with the annotations of 'voice+animation'. The instruments used in this study are the multimedia texts on "transgenesis method' which focuses on the processes involved in the "Protoplast Fusion' as well as the "Agro bacterium mediated transfusion' and a Comprehension Test that assessed the subjects understanding of the reading texts assigned. The neth hod of data analysis used is of descriptive statistics which uses the frequency count of the average (mean) value scores as well as the highest (max) and lowest score (min) in identifying the effectiveness of the multimedia annotations in facilitating the students comprehension level using the two presentational modes. Generally, the overall scores indicate that there is no significance difference in the use of annotations via the two presentational mode - 'text+animation7 and 'voice+animation' as the difference that exist in the scores are small. However, the findings do indicate that the subjects are found to emphasise on the use of their visual sense of modality in facilitating their reading tasks. Subsequently, this has resulted the students that are exposed to the presentational mode of 'text+animation' to do fairly better than the latter group 'voice+animation'. Finally, it is important to highlight here that the annotations (animations) found in the multimedia on-screen text, do to a certain extent, facilitate the students in understanding a science based text due to its ability to build referential connections between the two mental representations in short term memory hence, resulting in better performance in the tasks assigned